A kind of low-grade talcum powder and its preparation method and application
By mixing talc powder with abrasive and modifier, low-grade talc powder is prepared, which solves the problem of high processing cost of talc powder, and achieves a balance of hiding power and scrubbing resistance in building coatings, significantly reducing the cost of formula.
Patent Information
- Application Number
- CN202310242052.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-14
AI Technical Summary
The existing talc powder is expensive to process, which limits its use, and it is difficult to take into account the hiding power and scrubbing resistance of the coating film while reducing the cost of the construction coating formulation.
By mixing talc powder with abrasive solution, mixing and reacting with the modifier solution after ball milling, low-grade talc powder is prepared, and its D50 is controlled to be 16-18 μm, reducing the oil absorption and improving compatibility.
It realizes ultra-fine talc powder under low-cost processing conditions, reduces production energy consumption, and completely replaces kaolin in building coatings, taking into account hiding power and scrubbing resistance, significantly reducing the cost of formula.
Smart Images

Figure CN116218258B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of non-metallic minerals, and in particular to low-grade talcum powder and a preparation method and application thereof. Background Art
[0002] Talc is a common silicate mineral material, the lowest hardness among the mineral materials known in nature. It has a series of characteristics such as lubricity, fire resistance, acid resistance, insulation, high melting point, chemical inactivity, good hiding power, softness, good gloss, strong adsorption, etc. However, the high processing cost of talc powder currently severely limits its use. Therefore, how to achieve ultra-fine talc under low-cost processing conditions has always been one of the problems that the industry needs to solve urgently.
[0003] In economical architectural coatings, in order to reduce the cost of the formula and reduce the amount of titanium dioxide, a large amount of calcined kaolin is often added to improve hiding power. However, due to the large oil absorption of calcined kaolin, it has a great impact on the washability of the coating film. It is necessary to increase the content of emulsion to improve the washability, which invisibly increases the cost of the formula. After the two offset each other, the effect of reducing the cost of the formula is not very obvious. Therefore, how to take into account the hiding power and washability of the coating film while reducing the cost of the formula is one of the difficult problems in the industry. Summary of the invention
[0004] The purpose of the present invention is to provide a low-grade talcum powder and a preparation method and application thereof.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing low-grade talcum powder, comprising the following steps:
[0007] (1) mixing talcum powder with an abrasive solution and ball milling to obtain an intermediate product;
[0008] (2) The intermediate product is mixed with a modifier solution to react to obtain the low-grade talcum powder.
[0009] Preferably, the D50 of the talc is 16-18 μm.
[0010] Preferably, the abrasive solution comprises an abrasive and water; the mass volume ratio of the abrasive to water is 1 g: 5 to 10 mL.
[0011] Preferably, the abrasive comprises sodium polycarboxylate and polyvinyl alcohol; the mass ratio of the sodium polycarboxylate to polyvinyl alcohol is 1 to 3:1; the mass of the abrasive is 3 to 7‰ of the mass of talc.
[0012] Preferably, the ball milling media comprises steel balls with a diameter of 5 to 15 mm, steel balls with a diameter of 18 to 25 mm and steel balls with a diameter of 35 to 45 mm; the mass ratio of the steel balls with a diameter of 5 to 15 mm, the steel balls with a diameter of 18 to 25 mm and the steel balls with a diameter of 35 to 45 mm is 2 to 4:2 to 4:3 to 5; the ball milling media filling rate is 30 to 40%; and the ball milling time is 30 to 45 min.
[0013] Preferably, the modifier solution in step (2) comprises a modifier and water; the mass volume ratio of the modifier to water is 1 g: 1-3 mL; and the mass of the modifier is 5-10‰ of the mass of talc.
[0014] Preferably, the modifier comprises methacrylic acid and methacryloyloxysilane; the mass ratio of methacrylic acid to methacryloyloxysilane is 3 to 5:1.
[0015] Preferably, the temperature of the mixing reaction in step (2) is 100-120° C.; and the time of the mixing reaction is 30-40 min.
[0016] The invention also provides low-grade talcum powder obtained by the preparation method.
[0017] The invention also provides application of the low-grade talcum powder in architectural coatings.
[0018] The present invention has the following advantages:
[0019] The invention provides a method for preparing low-grade talcum powder, comprising the following steps: mixing talcum powder with an abrasive solution, and ball milling to obtain an intermediate product; and mixing the intermediate product with a modifier solution to obtain the low-grade talcum powder.
[0020] The present invention controls the fineness of talcum powder to achieve better fusion of talcum powder and grinding aid solution, thereby improving grinding efficiency. At the same time, due to the fineness, there is no need to perform crushing and grinding treatment in the ball mill, so the proportion of small-particle grinding media in the ball mill can be increased, thereby further improving the grinding efficiency. Compared with the traditional process for producing ultrafine talcum powder, the production energy consumption is greatly reduced.
[0021] The present invention also provides an application of low-grade talc powder in architectural coatings. The present invention selects low-grade talc with a silicon dioxide content of 20-30% as the raw ore, taking into account the grindability while reducing the oil absorption. The oil absorption of the product is further reduced through surface modification treatment, and the compatibility with downstream resins is improved. It is applied to the economical architectural coating formula, can completely replace the kaolin in the formula, taking into account the hiding power and washability of the coating film, and significantly reducing the formula cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a specific schematic diagram of the process of Example 1. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing low-grade talcum powder, comprising the following steps:
[0024] (1) mixing talcum powder with an abrasive solution and ball milling to obtain an intermediate product;
[0025] (2) The intermediate product is mixed with a modifier solution to react to obtain the low-grade talcum powder.
[0026] In the present invention, the talc ore is washed, dried and crushed in two stages to obtain talc powder particles, the talc powder particles are put into a ring roller mill for coarse grinding, and the talc powder is obtained after classification and collection.
[0027] In the present invention, the silicon dioxide content of the talc ore is preferably 20 to 30%, more preferably 23 to 27%, and even more preferably 24 to 26%.
[0028] In the present invention, the talc ore with a silicon dioxide content of 20-30% has higher hardness and better grindability, and the low-grade talc powder prepared by using it will also have lower oil absorption, and the product will have less impact on the washability of the coating when used downstream.
[0029] In the present invention, the diameter of the talc particles is preferably 10 to 30 mm, more preferably 15 to 25 mm, and even more preferably 18 to 22 mm.
[0030] In the present invention, the D50 of the talc powder in step (1) is preferably 16 to 18 μm, more preferably 16.5 to 17.5 μm, and more preferably 16.8 to 17.2 μm.
[0031] In the present invention, the material with talcum powder D50 of 16-18 μm is selected to reduce the crushing step in front of the traditional ball mill, and there is no need to divide the ball mill into compartments, and the whole compartment can be directly ultra-fine ground, which helps to improve the grinding efficiency of the material.
[0032] In the present invention, the abrasive solution comprises an abrasive and water.
[0033] In the present invention, the mass volume ratio of the abrasive to water is preferably 1 g: 5 to 10 mL, more preferably 1 g: 6 to 9 mL, and even more preferably 1 g: 7 to 8 mL.
[0034] In the present invention, the abrasive comprises sodium polycarboxylate and polyvinyl alcohol.
[0035] In the present invention, the mass ratio of the sodium polycarboxylate to the polyvinyl alcohol is preferably 1 to 3:1, more preferably 1.2 to 2.8:1, and even more preferably 1.5 to 2.5:1.
[0036] In the present invention, the mass of the abrasive is preferably 3-7‰ of the mass of talc, more preferably 4-6‰, and more preferably 4.5-5.5‰.
[0037] In the present invention, the abrasive solution is added during the process of the spiral auger conveying the talc powder.
[0038] In the present invention, the abrasive solution is preferably added by spraying.
[0039] In the present invention, talcum powder and abrasive solution are transported into a high-speed mixer via a spiral cutter for mixing.
[0040] In the present invention, the high shear force of the high mixer is used to make the contact between the grinding aid and the talc powder more complete and uniform, effectively avoiding the disadvantage that the grinding aid cannot be fully mixed in the spiral auger due to the small self-generated specific gravity of talc and the fluffy material.
[0041] In the present invention, the mixing time is preferably 10 to 20 minutes, more preferably 12 to 18 minutes, and even more preferably 14 to 16 minutes.
[0042] In the present invention, the next step of ball milling is carried out after the mixing in the high-speed mixer is completed.
[0043] In the present invention, the ball milling machine is preferably a single-chamber ball mill.
[0044] In the present invention, the volume of the ball bin of the single-bin ball mill is preferably 1.83×7.2m.
[0045] In the present invention, the ball mill media preferably include steel balls with a diameter of 5 to 15 mm, steel balls with a diameter of 18 to 25 mm, and steel balls with a diameter of 35 to 45 mm, and more preferably include steel balls with a diameter of 8 to 12 mm, steel balls with a diameter of 20 to 23 mm, and steel balls with a diameter of 38 to 42 mm, and more preferably include steel balls with a diameter of 9 to 11 mm, steel balls with a diameter of 21 to 22 mm, and steel balls with a diameter of 39 to 41 mm.
[0046] In the present invention, small-sized steel balls are selected for ultrafine grinding, which can further improve the grinding efficiency.
[0047] In the present invention, the mass ratio of the steel balls with a diameter of 5 to 15 mm, the steel balls with a diameter of 18 to 25 mm and the steel balls with a diameter of 35 to 45 mm is preferably 2 to 4: 2 to 4: 3 to 5, more preferably 2.2 to 3.8: 2.2 to 3.8: 3.5 to 4.5, and more preferably 2.5 to 3.5: 2.5 to 3.5: 3.8 to 4.2.
[0048] In the present invention, the medium filling rate of the ball mill is preferably 30-40%, more preferably 35-45%, and more preferably 38-42%; the ball milling time is preferably 30-45 min, more preferably 35-40 min, and more preferably 37-38 min.
[0049] In the present invention, the intermediate product is transported to a high-speed mixer with a controllable movable baffle plate through a spiral auger.
[0050] In the present invention, due to the low specific gravity of talcum powder, the material is easy to float and cannot fully contact with the modifier, thus affecting the modification effect. The top baffle of the high-speed mixer with controllable movable baffle will automatically move downward, compressing the space of the modification bin, increasing the probability of contact between the material and the modifier, and thus improving the modification effect.
[0051] In the present invention, the intermediate product is mixed with the modifier solution during the screw auger conveying process.
[0052] In the present invention, the modifier is preferably added in a spraying manner.
[0053] In the present invention, the modifier solution in step (2) comprises a modifier and water.
[0054] In the present invention, the mass volume ratio of the modifier to water is preferably 1 g: 1 to 3 mL, more preferably 1 g: 1.2 to 2.8 mL, and more preferably 1 g: 1.5 to 2.5 mL.
[0055] In the present invention, the mass of the modifier is preferably 5-10‰ of the mass of talc, more preferably 6-9‰, and even more preferably 7-8‰.
[0056] In the present invention, the modifier comprises methacrylic acid and methacryloxysilane.
[0057] In the present invention, the mass ratio of methacrylic acid to methacryloyloxysilane is preferably 3 to 5:1, more preferably 3.5 to 4.5:1, and even more preferably 3.8 to 4.2:1.
[0058] In the present invention, after the talcum powder is surface-modified, the compatibility of the talcum powder when used in downstream architectural coatings can be improved; after the talcum powder is coated with methyl propyloxy silane, it helps to improve the adhesion of the product, and when used downstream, it will improve the washability of the coating.
[0059] In the present invention, the temperature of the mixing reaction in step (2) is preferably 100-120°C, more preferably 105-115°C, and even more preferably 108-112°C.
[0060] In the present invention, the mixing reaction time is preferably 30 to 40 minutes, more preferably 32 to 38 minutes, and even more preferably 34 to 36 minutes.
[0061] In the present invention, the material obtained by the mixed reaction is placed in a cold mixer for stirring and cooling, and then placed in a spiral auger conveying device, and conveyed into a finished product silo for sieving, testing, and packaging to obtain the low-grade talcum powder.
[0062] In the present invention, the stirring speed is preferably 350-450 r / min, more preferably 380-420 r / min, more preferably 390-410 r / min; the stirring time is preferably 15-20 min, more preferably 16-19 min, more preferably 17-18 min.
[0063] In the present invention, the target temperature of the cooling is preferably 25 to 35°C, more preferably 27 to 33°C, and even more preferably 29 to 31°C.
[0064] The invention also provides low-grade talcum powder obtained by the preparation method.
[0065] The invention also provides application of the low-grade talcum powder in architectural coatings.
[0066] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0067] Example 1
[0068] 100 kg of low-grade talc ore with a silicon dioxide content of 20% was selected. After cleaning and natural drying, it was crushed by two stages of jaw crusher to obtain talc particles with a diameter of 10 mm. The talc particles were conveyed by belt into a ring roller mill for coarse grinding. After classification and collection, they entered the silo to obtain talc powder with a D50 of 17.02 um.
[0069] 150 g of sodium polycarboxylate and 150 g of polyvinyl alcohol were dissolved in 1.5 L of water to prepare an abrasive solution.
[0070] The talcum powder was put into the spiral auger, and the abrasive solution was added by spraying at the front end of the spiral auger, and then transported to the high-speed mixer with a controllable movable baffle for mixing for 10 minutes. After mixing, it was transported to a single-bin ball mill with a ball milling filling rate of 30% for ball milling for 30 minutes. The mass ratio of 10mm diameter steel balls: 20mm diameter steel balls: 40mm diameter steel balls in the ball milling medium is 3:3:4; after ball milling, it is classified and collected into the silo. The particle size of the intermediate product in the silo is 2.05um after testing.
[0071] 375 g of methacrylic acid and 125 g of methacryloyloxysilane were dissolved in 500 mL of water to prepare a modifier solution.
[0072] The intermediate product is conveyed into a talcum powder special modifier with a controllable movable baffle through a spiral auger, and the prepared modifier solution is added by spraying at the front end of the spiral auger conveying system. After modification at 100°C for 30 minutes, it enters the cold mixer and stirs at a speed of 400r / min for 15 minutes. The material temperature is 35°C, and it is conveyed into the finished product silo through a spiral auger for screening, testing, and packaging.
[0073] The specific process in this embodiment is as follows Figure 1 shown.
[0074] Example 2
[0075] 100kg of low-grade talc ore with a silicon dioxide content of 25% was selected. After cleaning and natural drying, it was crushed by two stages of jaw crusher to obtain talc particles with a diameter of 15mm. The talc particles were conveyed by belt into a ring roller mill for coarse grinding. After classification and collection, they entered the silo to obtain talc powder with a D50 of 16.88um.
[0076] 300 g of sodium polycarboxylate and 200 g of polyvinyl alcohol were dissolved in 2.5 L of water to prepare an abrasive solution.
[0077] 100kg of talcum powder was put into the spiral auger, and the abrasive solution was added to the front end of the spiral auger by spraying, and then transported to the high-speed mixer for mixing for 10 minutes. After mixing, it was transported to a single-chamber ball mill with a ball milling filling rate of 35% and ball milled for 35 minutes. The mass ratio of the ball milling medium is 3:3:4 for 10mm diameter steel ball: 20mm diameter steel ball: 40mm diameter steel ball; after ball milling, it was classified and collected into the silo to obtain an intermediate product with a particle size of D501.95um.
[0078] A modifier solution was prepared by dissolving 640 g of methacrylic acid and 160 g of methacryloxysilane in 1.6 L of water.
[0079] The intermediate product is conveyed into a talcum powder modifier with a controllable movable baffle through a spiral auger, and the prepared modifier solution is added by spraying at the front end of the spiral auger conveying system. After modification at 110°C for 35 minutes, the material enters the cold mixer and is stirred at a speed of 420r / min for 20 minutes. The material temperature is 32°C. After cooling, the material is conveyed into the finished product silo through a spiral auger for screening, testing and packaging.
[0080] Example 3
[0081] 100kg of low-grade talc ore with a silicon dioxide content of 28% was selected. After cleaning and natural drying, it was crushed by two stages of jaw crusher to obtain talc particles with a diameter of 18mm. The talc particles were conveyed by belt into a ring roller mill for coarse grinding. After classification and collection, they entered the silo to obtain talc powder with a D50 of 16.90um.
[0082] An abrasive solution was prepared by dissolving 400 g of sodium polycarboxylate and 300 g of polyvinyl alcohol in 3.5 L of water.
[0083] 100kg of talcum powder was put into the spiral auger, and the prepared abrasive solution was added to the front end of the spiral auger by spraying, and then transported to the high-speed mixer for mixing for 10 minutes. After mixing, it was transported to a single-chamber ball mill with a ball milling filling rate of 40% for ball milling for 40 minutes. The mass ratio of the ball milling medium is 3:3:4 for 10mm diameter steel ball: 20mm diameter steel ball: 40mm diameter steel ball; after ball milling, it was classified and collected into the silo to obtain an intermediate product with a particle size of D501.91um.
[0084] A modifier solution was prepared by dissolving 800 g of methacrylic acid and 200 g of methacryloxysilane in 3 L of water.
[0085] The intermediate product is conveyed by a spiral auger into a talcum powder special modifier with a controllable movable baffle, and the prepared modifier solution is added by spraying at the front end of the spiral auger conveying system. After modification at 120°C for 40 minutes, it enters the cold mixer and stirs at a speed of 430r / min for 20 minutes. The material temperature is 25°C, and it is conveyed by a spiral auger into the finished product silo for screening, testing and packaging.
[0086] The talcum powder prepared in the above Examples 1 to 3 was tested for relevant indicators according to GB / T15342-2012, and compared with the same type of products produced by traditional processes. The specific parameters are shown in Table 1.
[0087] Table 1 Test results of Examples 1 to 3
[0088] Example 1 Example 2 Example 3 Jet Milling Process Whiteness 91.35 91.52 91.44 91.40 D50(um) 2.05 1.95 1.91 1.97 Oil absorption (ml / 100g) 30 29 27 36 Moisture (%) 0.22 0.22 0.23 0.21
[0089] It can be seen from Table 1 that the talc powder prepared by the preparation method of the present invention has the same whiteness, fineness, moisture content, etc. as the ultrafine talc powder produced by the traditional airflow mill process, but the oil absorption is significantly lower than that of the talc powder produced by the traditional airflow mill process.
[0090] The talcum powder prepared in the above Examples 1 to 3 was applied to the economical architectural coating formula, completely replacing the kaolin in the formula and compared with the original formula, the formula is shown in Table 2. The test was carried out according to the relevant standards, and the results are shown in Table 3.
[0091] Table 2 Economical architectural coating formula
[0092]
[0093] Table 3 Test results of economical formula coatings
[0094]
[0095]
[0096] As can be seen from Table 3, the talcum powder prepared by the present invention can be used in the economical architectural coating formulation to completely replace kaolin. After reducing the emulsion content in the formulation, the hiding power, scrub resistance and alkali resistance of the paint film still meet the use requirements, effectively reducing the formulation cost.
[0097] As can be seen from the above embodiments, the present invention provides a low-grade talcum powder and a preparation method and application thereof, comprising the following steps: mixing talcum powder with an abrasive solution, ball milling to obtain an intermediate product; mixing the intermediate product with a modifier solution to obtain the low-grade talcum powder. As can be seen from Table 1, the talcum powder obtained by the preparation method of the present invention has a lower oil absorption than the talcum powder produced by the traditional airflow mill process; as can be seen from Table 3, the talcum powder prepared by the present invention is applied to the economical architectural coating formula, which can completely replace kaolin. After reducing the emulsion content in the formula, the properties of the paint film such as hiding power, scrub resistance and alkali resistance still meet the use requirements, effectively reducing the formula cost.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing low-grade talcum powder, characterized in that: The following steps are involved: (1) mixing talcum powder with an abrasive solution and ball milling to obtain an intermediate product; (2) mixing the intermediate product with a modifier solution to react to obtain the low-grade talcum powder; The D50 of the talc is 16-18 μm; The silicon dioxide content of the talc in step (1) is 20-30%; The ball milling media include steel balls with a diameter of 5 to 15 mm, steel balls with a diameter of 18 to 25 mm, and steel balls with a diameter of 35 to 45 mm; The mass ratio of the steel balls with a diameter of 5-15 mm, the steel balls with a diameter of 18-25 mm, and the steel balls with a diameter of 35-45 mm is 2-4:2-4:3-5; The medium filling rate of the ball mill is 30-40%; The ball milling time is 30 to 45 minutes; The temperature of the mixed reaction in step (2) is 100-120° C.; the time of the mixed reaction is 30-40 min; The modifier solution in step (2) comprises a modifier and water; The mass volume ratio of the modifier to water is 1g:1~3mL; The mass of the modifier is 5-10‰ of the mass of talc; The modifier comprises methacrylic acid and methacryloyloxysilane; The mass ratio of the methacrylic acid to the methacrylic acyloxysilane is 3-5:
1.
2. The preparation method according to claim 1, characterized in that The abrasive solution comprises an abrasive and water; The mass volume ratio of the abrasive to water is 1g:5-10mL.
3. The preparation method according to claim 2, characterized in that: The abrasive comprises sodium polycarboxylate and polyvinyl alcohol; The mass ratio of the sodium polycarboxylate to the polyvinyl alcohol is 1-3:1; The mass of the abrasive is 3-7‰ of the mass of talcum powder.
4. The low-grade talcum powder obtained by the preparation method according to any one of claims 1 to 3.
5. Use of the low-grade talc powder according to claim 4 in architectural coatings.
Citation Information
Patent Citations
Preparation method of talcum powder used for ship anticorrosion coatings
CN106366705A
Talc modifier and modification method thereof
CN109232984A